2016
DOI: 10.1159/000448519
|View full text |Cite
|
Sign up to set email alerts
|

Body Image Perception in Acromegaly Is Not Associated with Objective Acromegalic Changes but Depends on Depressive Symptoms

Abstract: Objective: Diagnosis of acromegaly is delayed up to 10 years after disease onset despite obvious external/objective changes such as bone and soft tissue deformities. We hypothesized that a lack of subjective perception of the disease state, possibly mediated by psychiatric or cognitive alterations, might contribute to the delayed initiation of a diagnostic workup. Design: Cross-sectional study. Methods: We investigated perceived body image by standardized questionnaires (FKB-20: Fragebogen zum Körperbild; FBeK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
(22 reference statements)
2
7
0
Order By: Relevance
“…Our findings are generally consistent with previous research on body image concerns in patients with acromegaly (Conaglen et al, 2015). However, our findings differ from those of previous studies regarding the association between anxiety, depression, and body image concerns (Dimopoulou et al, 2017). Previous studies suggest that body image perception in acromegaly correlates with depressive symptoms.…”
Section: Discussionsupporting
confidence: 77%
“…Our findings are generally consistent with previous research on body image concerns in patients with acromegaly (Conaglen et al, 2015). However, our findings differ from those of previous studies regarding the association between anxiety, depression, and body image concerns (Dimopoulou et al, 2017). Previous studies suggest that body image perception in acromegaly correlates with depressive symptoms.…”
Section: Discussionsupporting
confidence: 77%
“…The fact of having a rm diagnosis allowing a pharmacological and/or surgical treatment which has a positive in uence in the disease is felt as a gain, but it does not affect QoL. The present study also shows that patients present moderate to high levels of self-esteem, as also reported by Dimopoulu et al [22]. Changes at the facial level in acromegalic patients occur slowly and progressively, with people adapting to modi cations and accommodating its perception under a state of self-image acceptance.…”
Section: Discussionsupporting
confidence: 87%
“…These differences between symptoms and signs are in accordance with previous studies ( 12 ) that demonstrated up to 40% differences at the time of first presentation. Some authors suggest that the perceived body changes in acromegaly are less related to objective findings at the physical exam but more related to depressive symptoms ( 27 ). A recent study of the oro-dental state in acromegalic patients also reported a discrepancy between a relatively good objective exam and unsatisfactory self-assessment of oral health-related QoL ( 28 ).…”
Section: Discussionmentioning
confidence: 99%